2D Perovskites with Short Interlayer Distance for High‐Performance Solar Cell Application. Issue 22 (17th April 2018) - Ma, Chunqing; Shen, Dong; Ng, Tsz‐Wai; Lo, Ming‐Fai; Lee, Chun‐Sing
Abstract: 2D perovskites have emerged as one of the most promising photovoltaic materials owing to their excellent stability compared with their 3D counterparts. However, in typical 2D perovskites, the highly conductive inorganic layers are isolated by large organic cations leading to quantum confinement and thus inferior electrical conductivity across layers. To address this issue, the large organic cations are replaced with small propane‐1, 3‐diammonium (PDA) cations to reduce distance between the inorganic perovskite layers. As shown by optical characterizations, quantum confinement is no longer dominating in the PDA‐based 2D perovskites. This leads to considerable enhancement of charge transport as confirmed with electrochemical impedance spectroscopy, time‐resolved photoluminescence, and mobility measurements. The improved electric properties of the interlayer‐engineered 2D perovskites yield a power conversion efficiency of 13.0%. Furthermore, environmental stabilities of the PDA‐based 2D perovskites are improved. PDA‐based 2D perovskite solar cells (PSCs) with encapsulation can retain over 90% of their efficiency upon storage for over 1000 h, and PSCs without encapsulation can maintain their initial efficiency at 70 °C for over 100 h, which exhibit promising stabilities. These results reveal excellent optoelectronic properties and intrinsic stabilities of the layered perovskites with reduced interlayer distance. Abstract : 2D perovskites with reduced interlayer distance are synthesized by using propane‐1, 3‐diammonium (PDA). The quantum‐confinement effect that is usually observed in 2D perovskites is minimized in the engineered 2D perovskites, which facilitates charge transport between inorganic layers. With enhanced charge‐transport properties, PDA2 MA3 Pb4 I13 perovskite solar cells yield an efficiency up to 13.0% and exhibit better stability.